Postoperative reproductive outcomes in women with ovarian pregnancy: A retrospective analysis - Chian-Huey Wong; Yeou-Lih Wang; Jian-Pei Huang (Elsevier, 2021)
Objective: The reproductive outcomes of ovarian pregnancy are currently unknown. Therefore, the objective of our study was to report the pregnancy outcomes of women with laparoscopically treated ovarian pregnancy. Materials and methods: In this retrospective case analysis, unpublished cases of ovarian pregnancy between 2009 and 2016 were reviewed. Women were followed up for 3 years to obtain subsequent pregnancy data. Results: A total of 21 women who intended to become pregnant were included in this study. Predisposing risk factors for ovarian pregnancy including previous pelvic surgery (23.81%), presentation of pelvic endometriosis (23.81%), and prior intrauterine device insertion (9.52%) were identified. The major symptom at presentation was abdominal pain (85.71%), and no preoperative sonographic diagnosis of ovarian pregnancy was identified. Laparoscopic wedge resection was performed in most women (90.48%). During the 3-year follow-up period, spontaneous intrauterine pregnancy was observed in 13 women (61.90%), 2 women (9.52%) became pregnant through artificial insemination treatment, and 6 women are not able to get pregnant (28.57%). None of the women experienced recurrent ectopic pregnancy. Conclusion: The postoperative pregnancy outcomes of women with ovarian pregnancy were encouraging. In this study, the spontaneous intrauterine pregnancy rate was favorable, and no cases of recurrent ectopic pregnancy were reported.